Do Online Games Affect the Quality of Attachment Between Adolescents and Parents? - Tesaviani Kusumastiwi (Scientia Psychiatrica, 2020)
Online games are games using machines based on internet networks so that they can interact between players and can be accessed either via computers, console games or smartphones. This game is top-rated not only apart from the challenges that exist in the game, as well as the interaction with other players, so it resembles real life. Ease of access and fun games cause online game users to take more and more time to play online games. This behaviour makes online game users neglect their daily activities and reduce interaction with the real world. Adolescence is an age that is prone to addiction to online games due to various factors. The attachment of parents and adolescents is allegedly able to play a role as a preventive factor and symptom improvement in online gaming disorder in adolescence.